Changes of trade patterns of the baltic states in the context of the european union integration - Cipkute, Eivile (2016)
International trade is the key element of globalization and closer economic and political cooperation between the countries. The thesis focuses on analyzing the regional integration effects on the trade patterns of the members of regional trading blocs. The analysis focuses on the EU as the regional formation, and the Baltic States as the members of this union. The Baltic States have undergone unique economic and political developments since gaining independence after the Soviet Union collapsed. Lessons learned from the Baltic States’ experience are unique and valuable for other countries and regions, which are undergoing similar transformations. The main research method used in the thesis is the gravity model of trade, which rests on the key assumption that trade between the countries is defined by the size of the economies and the distance between the countries. The gravity equation estimates showed that the membership of the Baltic States in the EU had a positive and significant effect on the export levels of the Baltic States to other EU members. On the other hand, the membership in the EU is not the main trade stimulating factor. The more important factor for the Baltic States’ exports is the common history of belonging to the former Soviet Union. Therefore, the longer lasting ties still remain important trade creating factors for the Baltic States. At the same time, analysis revealed that the economic ties of the Baltic States with the former Soviet Union members was diminishing significantly over time.